Penerapan Metode Six Sigma di PT Triangle Motorindo - Arfan Bakhtiar; Bintang Rachvadani Dzakwan; Murni Elfrida Br Sipayung; Claudha Alba Pradhana (OPSI, 2020)
PT. Triangle Motorindo is the sole agent holder of the VIAR Brand as one of the largest manufacturers of three-wheeled motorcycles in Indonesia. This company was founded in 2000 and has grown as one of the largest manufacturers of three-wheeled motorcycles in Indonesia. As one of the largest producers of three-wheeled motorbikes in Indonesia, PT Triangle Motorindo must be able to maintain and continue to improve the quality of their products in order to remain strong in the competition. In the production process, this company needs to reduce the number of defects that often occur in the production process, so that it decides to use the Six Sigma method to overcome these problems. Six Sigma is a statistical concept that measures a process related to defects or damage. Reaching six sigma means that a process generates only 3.4 defects per million chance, in other words, that it is running almost perfectly. The company is in a position where the defect type reaches 3.55 sigma. Therefore, the DMAIC method is used to increase it to 4 sigma. After the improvement stage is carried out, the company is expected to be able to reach the 4 sigma stage